The relationship between restaurant ambience and customers’ satisfaction in Shah Alam Arabic Restaurants, Selangor - Omar, Muhamad Saufiyudin; Ariffin, Hashim Fadzil; Ahmad, Rozila (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
Restaurant ambience plays an important role in establishing a restaurant image, and to attract customers to dine.Exterior and interior design that is eye-catching will pull the customer to visit the restaurants.The purpose of this study is to examine the relationship between restaurant ambience and customer satisfaction in the Arabic restaurants.This study also seeks to determine which restaurant ambience elements highly influence customer satisfaction.The elements of spatial layout, interior design, colour and music were measured. Quantitative data were collected from 411 respondents in Shah Alam, Selangor. It was found that colour is the element that is significantly and mostly influences customers‟ satisfaction. More detailed findings and implications are also discussed.